2013
DOI: 10.1097/sle.0b013e31828e3b9d
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic Colectomy for Obstructive Colorectal Carcinoma

Abstract: Laparoscopic surgery for obstructive colorectal carcinoma is a controversial issue. Defining the obstructive carcinoma as colonoscopic impassability, the patients with obstructive carcinoma were managed according to the treatment algorithm, by which the indication of open or laparoscopic surgery was determined. As a result, 31 patients with obstructive colorectal carcinoma underwent laparoscopic surgery. The location of the tumor was in the right side in 10 patients and in the left in 21 patients. Preoperative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
1

Year Published

2015
2015
2016
2016

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 15 publications
0
0
1
Order By: Relevance
“…In a comparison of laparoscopic surgery and conventional laparotomy in obstructed colon cancer, Abe et al reported that laparoscopic surgery could also result in the retrieval of an oncologically acceptable number of lymph nodes [18]. In this study, we showed no significant difference in the number of retrieved lymph nodes or operative time.…”
Section: Discussioncontrasting
confidence: 33%
“…In a comparison of laparoscopic surgery and conventional laparotomy in obstructed colon cancer, Abe et al reported that laparoscopic surgery could also result in the retrieval of an oncologically acceptable number of lymph nodes [18]. In this study, we showed no significant difference in the number of retrieved lymph nodes or operative time.…”
Section: Discussioncontrasting
confidence: 33%